Rancang Bangun Smart Pet Feeder Berbasis IoT Menggunakan Blynk - Wahid Wahyudin; Lukman Rosyidi; Salman El Farisi (DBESTI: Journal of Digital Business and Technology Innovation, 2026)
Many pet owners struggle to feed their pets regularly due to busy schedules and limited time. This can negatively impact the health of the pets. To address this problem, this study designed an Internet of Things (IoT)-based Smart Pet Feeder system that can dispense food automatically or manually and monitor food availability in real time via the Blynk application. The system uses a Wemos D1 ESP8266 microcontroller, a servo motor, an ultrasonic sensor, and an RTC module for scheduling. The research was conducted in stages: needs analysis, system design, implementation, and hardware and software testing. The Blynk application serves as a user interface for setting feeding schedules, viewing the current time, and receiving notifications when the feed level is low. Test results show that the system functions as intended, with a 100% success rate for both automatic and manual feeding, and a sensor accuracy of 97.91%. This system offers a practical solution for efficient and flexible pet feeding management.